Peningkatan Kualitas Pelaku UMKM pada Era Digital melalui Pelatihan Pengembangan Merek Dagang (Brand) UMKM di Kelurahan Kembangan Selatan - Putra, Muhammad Syah Irsan Ratu; Cicilia, Orlin (EQUATOR SINAR AKADEMIA, 2025)
Indonesian economy continues to grow positively amidst increasingly uncertain global conditions, including tariff wars initiated by the United States against several countries, as well as physical warfare in several regions that have disrupted global economic activity. The positive growth in Indonesia is driven by the MSME sector. South Kembangan is a densely populated urban village, with an estimated population of around 35,000 by 2024. Based on the national ratio of MSMEs to the population, an estimated 23%, or approximately 8,000 residents, of South Kembangan are involved in the MSME sector. A common problem faced by MSMEs is marketing, which is closely related to the brand of the products and/or services offered. A business's brand can directly influence product and/or service sales; a strong brand will increase sales, while a weak one will decrease sales. Therefore, the Faculty of Economics and Business of Mercubuana University, together with the South Kembangan Village, West Jakarta, DKI Jakarta, collaborated to conduct a Community Service Activity with the theme